A FAMILY WITH MANY PROBLEMS IN THE SOCIAL SUPPORT SYSTEM - Matejek, Józefa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The contemporary family is subject to significant transformations, which forces its members to adapt in new conditions of social functioning. Changing socio-economic conditions, difficult financial situation, helplessness, occurrence of addictions and social pathologies often make families unable to properly fulfill their tasks and functions. Social support can refer to taking action in any difficult situation in which a person is - a family who can not cope independently under the circumstances. The family is one of the most important values in human life, therefore the possibilities of its support should be broad, varied and generally available.The aim of the study is to present selected aspects and forms of social support for the family, which experiences many problems in everyday functioning. Supportive activities concern, among other things: the form of social assistance that the family will receive in the light of legal acts, the types of benefits a family can get in a difficult life situation and diversified forms of assistance and support from specialists for working with family - social workers and family assistants. The study uses the method of analysis of existing data (desk research), the research has been given a diagnostic and descriptive character. In the presented article, the analysis covered the subject literature on the subject matter covered, applicable legal acts, statistics, government reports and reports on social assistance benefits. The collected material was supplemented by an expert interview conducted with social workers and family assistant. Undertaken assistance activities should support families not only in the traditional social role, but also be open to the dynamics of socio-economic and cultural changes and new areas requiring assistance. Therefore, when undertaking supporting activities, one should focus both on preventing negative phenomena that may threaten the proper functioning of the family and effectively eliminate the effects of their occurrence.